Tuesday

March 3, 2015

March 3, 2015

Posted by **Jordan** on Sunday, August 29, 2010 at 9:09pm.

X1=

X2=

2.)\sqrt{7 x - 9} + 6 = 3x

there are two solutions

3.)4 <= 5 x - 4 <10

4.)(x/4x-16)-7 = (1/x-4)

5.) (1/R) = (1/R1)+ (1/R2)

for R1

- Math/College Algebra -
**MathMate**, Monday, August 30, 2010 at 8:30amI'll do the first one. Will be glad to critique if you show the work for the rest.

3 x^2 + 4 x - 1 = 0

divide by 3 throughout:

x² + (4/3)x - (1/3) = 0

(x+2/3)²-(2/3)²-(1/3)=0

(x+2/3)² = 7/9

x+2/3 = ±(√7)/3

x = -2/3 ±(√7)/3

Note: you'd be better off posting the questions in separate posts. There will be more chance that some of them get answered sooner.

**Answer this Question**

**Related Questions**

Math - I am given 4 choices for the problem the square root of 8x -2 = the ...

Algebra II - 1)What method(s) would you choose to solve the equation: x2 + 2x - ...

algebra - determine the nature of the solutions of the equation, one real ...

algebra - determine the nature of the solutions of the equation. Two real ...

Algebra - For the following equation, state the value of the discriminant and ...

math - solve 2x^2+3x+8=0 and express the solutions in a+bi form. Let's use the ...

Math - For the following equation, state the value of the discriminant and then ...

Algebra - Consider the equation: 4x^2 – 16x + 25 = 0 (a) Show how to compute the...

Algebra - Consider the equation 4x^2 – 16x + 25 = 0. (a) Show how to compute the...

algebra - For the following equation, state the value of the discriminant and ...